Adhesive free-standing multilayer films containing sulfated levan for biomedical applications - TOKSOY ÖNER, EBRU (ELSEVIER SCI LTD, 2018)
This work is the first reporting the use of layer-by-layer to produce adhesive free-standing (FS) films fully produced using natural-based macromolecules: chitosan (CHI), alginate (ALG) and sulfated levan (L-S). The deposition conditions of the natural polymers were studied through zeta potential measurements and quartz crystal microbalance with dissipation monitoring analysis. The properties of the FS films were evaluated and compared with the control ones composed of only CHI and ALG in order to assess the influence of levan polysaccharide introduced in the multilayers. Tensile tests, dynamic mechanical analysis and single lap shear strength tests were performed to evaluate the mechanical properties of the prepared FS films. The presence of L-S conferred both higher tensile strength and shear strength to the developed FS membranes. The results showed an adhesion strength 4 times higher than the control (CHI/ALG) FS films demonstrating the adhesive character of the FS films containing L-S. Morphological and topography studies were carried out revealing that the crosslinking reaction granted the L-S based FS film with a higher roughness and surface homogeneity. Preliminary biological assays were performed by cultivating myoblasts cells on the surface of the produced FS films. Both crosslinked and uncrosslinked FS films containing L-S were cytocompatible and myoconductive. (C) 2018 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Sulfated levan; Free-standing membranes; Adhesiveness; Biomedical applications; GENIPIN CROSS-LINKING; POLYSACCHARIDE NANOSHEET; VISCOELASTIC PROPERTIES; CHITOSAN MEMBRANES; CELLULAR ADHESION; HYALURONIC-ACID; ALGINATE; CELLS; MICROENVIRONMENTS; DIFFERENTIATION